2021
DOI: 10.1136/bmjoq-2021-001403
|View full text |Cite
|
Sign up to set email alerts
|

Constructing high-quality rest facilities to maximise performance and ensure patient safety

Abstract: IntroductionJunior doctors are working in an increasingly overstretched National Health Service. In 2018, Kettering General Hospital (KGH) was awarded £60 800 of government funds to create high-quality rest facilities and improve junior doctor well-being.MethodsAn audit and survey in KGH identified the structural and functional improvements needed. From November 2019 to June 2020, £47 841.24 was spent on creating new rest facilities. On completion, a postaction review assessed how the changes impacted morale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…This helps me to feel more relaxed and enhances my mood.” However, because this study assessed all clinic staff, the data regarding physician perceptions were highly limited. Residents were asked about their well-being following the establishment of a new relaxation center that was quiet and had low light for resting and/or studying (Silva et al, 2021). They found a large increase in residents’ ability to rest during breaks and that the residents found the new space to be relaxing and restful.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This helps me to feel more relaxed and enhances my mood.” However, because this study assessed all clinic staff, the data regarding physician perceptions were highly limited. Residents were asked about their well-being following the establishment of a new relaxation center that was quiet and had low light for resting and/or studying (Silva et al, 2021). They found a large increase in residents’ ability to rest during breaks and that the residents found the new space to be relaxing and restful.…”
Section: Resultsmentioning
confidence: 99%
“…Of the sixteen studies that met the inclusion criteria, all had been found in peer-reviewed journals. Nine were conducted in Europe (Björndell & Premberg, 2021; Brambilla et al, 2020; Rice et al, 2008; Lupo et al, 2021; Pleban et al, 2021; Raffier-Peres & Estryn-Behar, 2015; Ratnapalan et al, 2011; Sen et al, 2018; Silva et al, 2021), three in East Asia (Lin et al, 2013; Waroonkun, 2020; Wu et al, 2008), two in the Middle East (Jalili et al, 2013; Kebapcı & Güner, 2021) and one each in Brazil (Marques et al, 2018) and South Africa (Folscher et al, 2015). Notably, none of the studies that met the inclusion criteria had been conducted in the United States, indicating a significant gap in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PFA training can improve basic psychological skills in frontline workers [ 37 ], and is advocated for those working in high-risk environments, such as the healthcare setting [ 38 ]. Work breaks are recognised as key to fostering a caring environment by preventing stress, burnout, and compassion fatigue [ 39 ], and the provision of high-quality rest spaces has been shown to impact on staff morale, well-being, and quality of patient care [ 1 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…PFA training can improve basic psychological skills in frontline workers [37], and is advocated for those working in high-risk environments, such as the healthcare setting [38]. Work breaks are recognised as key to fostering a caring environment by preventing stress, burnout, and compassion fatigue [39], and the provision of high-quality rest spaces has been shown to impact on staff morale, wellbeing, and quality of patient care [1,40].…”
mentioning
confidence: 99%